Analisis Didaktik Calon Katekisasi Sidi Untuk Pendewasaan Iman Warga Gereja di Jemaat Gmim Sion Picuan Minahasa Selatan - Eremtrouw Pattinasarany; Semuel Selanno; Wolter Weol (Peneliti.net, 2021)
One of the services carried out by the Christian Church in Indonesia (GMIM) is Catechization (Sidi). In order to become a man who has more faith in Christ, he needs to be educated and educate himself.